2002
DOI: 10.1111/1467-7687.00237
|View full text |Cite
|
Sign up to set email alerts
|

Newborns’ preference for up–down asymmetrical configurations

Abstract: The present study was aimed at investigating whether, because of a differential sensitivity between the upper and the lower visual fields, in a visual preference task newborns would orient more frequently and look longer at patterns with a great number of high-contrast areas in the upper or lower visual field. Newborns were presented with three pairs of geometrical stimuli, each composed of a pattern with a greater number of elements in the upper part or a pattern with more elements in the lower part. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 45 publications
10
108
2
Order By: Relevance
“…The results of Experiment 1 contradict the prediction drawn from the account that explains newborns' face preference only by a nonspecific bias toward top-heavy stimuli (3). Although all conditions in Experiment 1 contrasted an ''upright'' and an ''inverted'' configuration, the newborns displayed selective preference only in two of these contrasts.…”
Section: Methodscontrasting
confidence: 62%
See 1 more Smart Citation
“…The results of Experiment 1 contradict the prediction drawn from the account that explains newborns' face preference only by a nonspecific bias toward top-heavy stimuli (3). Although all conditions in Experiment 1 contrasted an ''upright'' and an ''inverted'' configuration, the newborns displayed selective preference only in two of these contrasts.…”
Section: Methodscontrasting
confidence: 62%
“…However, controversy remains as to whether this preference is based on one or more nonspecific biases in the newborn's visual system that happen to maximally respond to faces or whether the underlying mechanisms are stimulusspecific (1,3). This issue is important to debates in several fields, including developmental psychology and cognitive neuroscience.…”
mentioning
confidence: 99%
“…Pair 2 -a top-heavy and a bottom-heavy non-face configuration-was presented in order to verify if the attentional bias toward top-heavy non face patterns, as has been found with newborns ( Simion et al, 2002 ), is still active to any extent in 3-month-old infants. Understanding the power of the top-heavy property in inducing a preference for non-face-like stimuli was necessary for interpreting the role of the top-heavy property in producing the face preference predicted to be observed in Pair 1, as well as for making previsions regarding the possible outcome for the direct comparison performed in Pair 3 between an upright face and a top-heavy non-face pattern.…”
Section: Behavioural Studymentioning
confidence: 99%
“…This work showed that newborns' face preference derives from a number of more general attentional biases that cause certain structural properties of a visual stimulus to be preferred, rather than from a content-determined bias for the unique geometry of the face ( Simion, Macchi Cassia, Turati & Valenza, 2003 ). In fact, much evidence is now available supporting the contention that the visual structural properties embedded in the face are capable of producing a preferential response also when they are embedded in non-face stimuli ( Macchi Cassia, Valenza, Pividori & Simion, 2002;Simion, Valenza, Macchi Cassia, Turati & Umiltà, 2002 ). Specifically, one of these structural properties (i.e., up-down asymmetry) relates to the up-down asymmetrical distribution of the inner facial features along the horizontal plane (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation